Den metriske tilpasning - Brink, Lars (Studier i Nordisk, 2022)
Poetic meter is the set of prerequisites for how stressed and unstressed syllables should be arranged as a rule. The poet’s metrical adaptation aims to make the shades of stress in the language fit. This appears to be simple, since in all European traditions every traditionally defined heavy stress can be placed in unstressed position, while every secondary or light stress can be placed in accentuated positions (not to mention unaccentuated; thus “anything goes”). Nevertheless, we all know it is possible to commit metrical errors in poetic composition. There must then be an adaptation rule that cannot be broken. This rule is: Inversion is not allowed. A common phrase in daily speech with a well-defined stress pattern cannot have the opposite pattern in poetic meter. In Cole Porter’s famous lines I love Paris in the Springtime (the meter begins with two trochees) I love Paris in the fall ‘Paris’ could not be ‘Madrid’, since Madrid would require the opposite accentuation pattern than what occurs in daily speech.